2020
DOI: 10.1016/j.chom.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for a Convergent Immune Response against Ebola Virus

Abstract: Highlights d People exposed to the GP spike complex of EBOV develop V H 3-15/V l 1-40 mAbs d Cryo-EM reveals V H 3-15/V l 1-40 mAbs target the NPC1receptor binding site on GP d V H 3-15/V l 1-40 mAbs avoid using CDRH3 and mostly utilize the light chain for binding d Key interacting residues used by V H 3-15/V l 1-40 mAbs are already encoded by germline genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Antibodies that share the same germline gene usage and similar molecular interactions with antigens have been observed in other viral infections, including Ebola, Zika, and influenza, as well as chronic HIV-1 infection. The VH3-15/VL1-40-based class of antibodies targeting the NPC1-receptor-binding site on Ebola GP has been reported as a common response in individuals infected with the Ebola virus or vaccinated with Ebola virus vaccine rVSV-ZEBOV [38,39]. The VH3-23/VK1-5 antibodies specifically recognize the lateral ridge of ZIKV EDIII [40].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies that share the same germline gene usage and similar molecular interactions with antigens have been observed in other viral infections, including Ebola, Zika, and influenza, as well as chronic HIV-1 infection. The VH3-15/VL1-40-based class of antibodies targeting the NPC1-receptor-binding site on Ebola GP has been reported as a common response in individuals infected with the Ebola virus or vaccinated with Ebola virus vaccine rVSV-ZEBOV [38,39]. The VH3-23/VK1-5 antibodies specifically recognize the lateral ridge of ZIKV EDIII [40].…”
Section: Discussionmentioning
confidence: 99%
“…The IGHV germline of ERBs contains numerous gene expansions relative to human orthologs (Figure 1). We observed that several of the ERB IGHV genes present, and, in some cases, expanded, were associated with V(D)J rearrangement signatures for specific pathogens (Table S1; Cohen-Dvashi et al, 2020;Watson et al, 2017), suggesting that the ERB may be equipped with an IGHV repertoire prone to generating antibodies that can bind to zoonotic viruses. The expansion of the IGHJ4 genes in ERBs may reflect its important role in V(D)J recombination; however, its impact in B cell diversity and antibody specificity is still unknown (Arnaout et al, 2011).…”
Section: Distinct Features Found On the Igh Locusmentioning
confidence: 94%
“…For instance, the VRC01 class of HIV-specific antibodies often have a motif that includes a 5-residue LCDR3 and a short and flexible LCDR1 [39][40][41][42] . Importantly, recent work has identified a public clonotype targeting the Ebola virus glycoprotein (GP) that is elicited after natural infection or vaccination 43,44 . These GP-specific antibodies are encoded by IGHV3-15 and IGLV1-40, make conserved light chain and heavy chain contacts with GP, and have been isolated from multiple individuals.…”
Section: Discussionmentioning
confidence: 99%